Evaluating proFamilies-dementia: Adopting photovoice to capture clinical significance. (September 2013) - Guerra, Sara R; Rodrigues, Sofia P; Demain, Sara; Figueiredo, Daniela M; Sousa, Liliana X
Dementia is a challenging chronic illness that affects the patients and their families. Families often perform a full-time, specialised role, which requires expert knowledge and skills. This paper describes the evaluation of proFamilies-dementia (a programme developed to support families that care for a relative with dementia) using an innovative participatory methodology: photovoice, a qualitative method of research that uses photography and voice to access people's experiences. The programme was evaluated in order to identify the positive and negative impacts of the intervention on individuals and families; the advantages and disadvantages of photovoice as a participatory tool were also captured. The sample consisted of six people from five families. Participants identified only positive impacts of the programme, including better emotional management, normalisation of feelings and increased focus on self-care. Photovoice facilitated access to the process of change initiated by proFamilies-dementia, described by a process of going beyond illness, negativity and loneliness.